Costa Rica : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2002 Article IV Consultation highlights that since 2000, economic growth in Costa Rica has slowed to about 2 percent. Inflation has remained at 10 percent, and unemployment has remained at about 6 percent. The external current account deficit has increased to about 5.5 percent of GDP, reflecting a sharp increase in imports of capital goods by public enterprises, and a loss of dynamism of exports, associated in part with some weakening of international competitiveness. Progress in other areas of structural reform has also slowed in recent years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet